PWE-030 High definition (hd) endoscopy but not i-scan significantly increases the detection of markers of coeliac disease: a multicentre uk study. (22nd June 2015) - Burden, M; Mooney, PD; Patel, N; Wong, S; Teare, J; Hadjivassiliou, M; Sanders, DS
Abstract : Introduction: Coeliac disease (CD) remains underdiagnosed. Many patients with CD have undergone a previous endoscopy where the opportunity to make a diagnosis was missed. Clinicians may rely on endoscopic markers of CD to guide biopsy but they lack sensitivity. A routine duodenal biopsy approach may solve this problem but it is expensive. Methods to improve the detection of CD at endoscopy to guide biopsy would seem advantageous. I-Scan, a digital enhancement technique, has shown promising results. However, only one, single centre study has been performed. This was an uncontrolled, unblinded trial in high prevalence population (35% CD). We aimed to assess the utility of I-Scan in a lower prevalence population in a randomised controlled trial Method: Patients from 2 UK hospitals (Royal Hallamshire Hospital, Sheffield and St. Mary's Hospital, London) were randomised into 2 groups: Group 1 standard HD white light endoscopy (WLE) and Group 2 WLE plus I-Scan. Patients were compared to a standard non-HD WLE control group, Group 3. All patients received at least 4 duodenal biopsies. Coeliac serology was performed concurrently. The presence of endoscopic markers of CD, scalloping, mosaic pattern, nodularity, loss of duodenal folds or increased vascularity was noted and compared to VA on histology as the gold standard Results: 700 patients (63% female, mean age 51.7) were recruited (201 into Group 1, 199 in Group 2 and 300 into Group 3). In total 130 (18.5%) new diagnoses of CD were made (19 in Group 1, 22 in Group 2 and 89 in Group 3). In new CD cases, endoscopic markers of CD were seen in 80.5% in the HD groups compared to 41.6% in Group 3 (p < 0.0001). In Group 2, I-Scan appeared to enhance changes in 18% of new CD cases. However there was no significant difference in sensitivity between Group 1 (89.5%) and Group 2 (72.7%) (p = 0.2). Full sensitivity and specificity analysis is shown in Table 1 . The severity of VA was analysed for missed cases. There was no significant difference in the distribution of VA severity across the 3 groups (p = 0.6). The use of HD/I-Scan did not prevent total VA being missed Conclusion: HD endoscopy significantly increases the detection of the endoscopic markers of CD (p < 0.0001). However although I-scan appears to enhance the changes of villous atrophy it does not significantly increase the detection of markers (p = 0.2) Disclosure of interest: None Declared.